Education Based on A Collaborative Approach with The Pottery Community for Students’ Art Learning - Fajrie, Nur; Azhari, Mohamed Nor; Purbasari, Imaniar; Harmanto, Dwi (International Journal of Elementary Education, 2022)
This study discusses about collaborative education in MBKM program entrepreneurship activities in art learning for Elementary School Teacher Study Program students. The purpose of the study is to analyze the process and results of art learning with the pottery community. The research approach uses action research with an exploratory design. The participants were ten PGSD students. Data collection methods are interviews, observation of the process followed by an understanding questionnaire and a test of artistic practice. Data analysis through description and interpretation of social situation processes and explaining interventions in research. The planning stage is carried out with discussions and input from potters as practitioners. The learning outcomes of appreciation aspects from various cycles have increased from high to very high category by 10%, the medium for high category has increased by 89%. The achievement of the creative aspects of the pretest and posttest results showed a significance level of 0 < 0.05. The impact of influence can be accepted with a collaborative approach. Creative ideas tend to create traditional children's toys and household products from clay. The art learning results have increased in understanding the concept of procedures and characteristics of working materials. The students’ ability have increased their skills in making works of art with clay media. The findings from the research can contribute to the theoretical concept of local culture-based art learning and can practically add to students' artistic experience in preserving the local culture of the surrounding community.